Solomon Islands Systematic Country Diagnostic : Priorities for Supporting Poverty Reduction and Promoting Shared Prosperity - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
Solomon Islands is a small, remote archipelago in the South Pacific that faces a fairly unique set of development challenges. Solomon Islands is now at a critical juncture in its development trajectory. Neither the economic geography nor the present political economy of Solomon Islands is particularly conducive to the establishment of state institutions capable of managing upcoming socioeconomic change. Because of the weaknesses of state institutions, and consistent with Solom on Islands’ historical experience, a variety of non-state and international actors will need to play important roles in managing upcoming and potentially risky socioeconomic change. This Systematic Country Diagnostic (SCD) for Solomon Islands identifies key challenges and opportunities for achieving inclusive and sustainable growth, to accelerate progress toward the World Bank Group’s twin goals of reducing extreme poverty and promoting shared prosperity.